The Relationship Between Low Birth Weight (LBW) and Basic Immunization Status with the Incidence of Stunting in Toddlers - Grace Carol Sipasulta; Dahniar Dahlan; Sirajul Muna; Resty Noflidaputri (CV. Get Press Indonesia, 2025)
Stunting is a chronic nutritional problem that has a serious impact on children's growth and development. This study aims to determine the relationship between low birth weight (LBW) and basic immunization status with the incidence of stunting in toddlers in the Selayo Public Health, Solok Regency in 2019. The study used a case-control design with 58 respondents (29 stunted, 29 not stunted) selected by purposive sampling. Data were obtained through interviews and observations of KIA books, analyzed using the Chi-Square test at a 95% confidence level. The results showed a significant relationship between LBW and the incidence of stunting (p = 0.047; OR = 3.9) and between incomplete basic immunization status and stunting (p = 0.029; OR = 4.1). It was concluded that LBW and basic immunization status play an important role in increasing the risk of stunting. The implications of this study encourage increased nutrition education for pregnant women and the implementation of complete basic immunization to reduce the prevalence of stunting.